Sarana Kohesi Leksikalparagraf Mahasiswa Program Studi Manajemen Universitas Mathla’ul Anwar - Maulana, Nanang (Jurnal Artikula, 2020)
This research was carried out in the Management Study Program of the Faculty of Economics, Mathla'ul Anwar University in the compulsory general subject (MKWU) of Indonesian Language which aims to determine the ability of students in preparing paragraphs as well as the use of lexical cohesion tools. From the results of the analysis found four types of repetition include repetition of types that have an impact, intact, partially and change the sound. Repeated types of repetition get the largest number of 15, followed by the type of repetition of the total number of 13, some with the number 5 and change the number of sounds 2. The method used in this research is descriptive analytic. This method is done by collecting data, compiling or classifying data, analyzing and then trying to describe linguistic data in the form of written Indonesian sentences.